Organisational Adaptations A Pluralistic Perspective - Adegbite, Oluwaseun E. (SpringerBriefs in Business,, 2018)
This book explores how enterprises adapt to challenges in their business environments. It focuses on the critical elements within organisations that every executive must address in order to remain competitive. It takes a pluralist approach in trying to broaden our knowledge on organisational adaptations. It also offers an exploratory delve into existing literature of organisational study. This is biased for content, context and process framework and processual analytic approach in order to identify, determine, understand the intricacies of adaptations going on in various business organisations. The book also includes a case study of how Kodak and Fujifilm responded to digitalisation of photographic film industry, which is an example of major adaptation change. Many global brands are often contending with similar issues and real life challenges. Simply put, today's business environment demands a new way of doing business that challenges brand's existing core business philosophy. Organisations are 'individual' entities in their own rights. Businesses have devised ways of surviving their environments. They do this by downsizing, merger and acquisition, business ecosystems, other forms of collaborations and strategic alliances. While this is true, current research works into generic predictors and/or concepts that enhance the transformation process are scarce. It is particularly important to align the theories and concepts of organisational adaptations with realities in the business environment. This book delves deep and explains adaptations in organisations, but also offers insight for how executives can adapt and thrive in their dynamic business environments. .